Basil: Hinduism Belief and Herbal Use - Kham-Ek, Paramath (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
Holy basil is an interesting and sacred plant in Hinduism for beliefs and medicinal uses. Thais who live in India either do not know or have not studied Indian culture well; they may use holy basil for cooking without thinking about beliefs. The basil is incarnation of goddess Lakṣmī, Lord Vishnu’s consort, in this human world. Her epithet is Tulsī. Her incarnation has a story. Therefore, Indian people in Vaishnavism respect and worship holy basil as a very sacred plant. They often plant the holy basil in their house, ashrams and around shrines to turn evil into good, as well as to prevent the Yum's crony from entering the house. Usually the Basil plant is used in sacred ceremonies (Sanskāra) such as when a sinful person dies, at the time of cremation, if the branches of the holy basil are placed on the corpse or the soil around the basil plant is rubbed on the body then the soul will become pure, and will go to heaven instead of hell. Basil is used in Upanāyana Sanskāra (one of a sacred ceremony of 12 Sanskāras) that is when a son has reached a suitable age, he is brought to the teacher’s resident to become his student. In addition, Indian people believe that worshipers of holy basil will have good fortune, wealth, good health, there will be children and child birth. The holy basil is also used to make rosary for prayer to ward off various dangers. Aside from belief, holy basil is an herbal medicine for treating various diseases, from ancient times to the present day, such as the treatment of disability, body odor, nourishing the heart, coughing, and diarrhea. Make the face shine bright and prevent cancer, etc.